A haplotype-based evolutionary history of barley domestication - Yu Guo; Murukarthick Jayakodi; Axel Himmelbach; Erez Ben-Yosef; Uri Davidovich; Michal David; Anat Hartmann-Shenkman; Mordechai Kislev; Tzion Fahima; Verena J. Schuenemann; Ella Reiter; Johannes Krause; et al. (Nature, 2025)
Abstract Barley is one of the oldest cultivated crops, with a complex evolutionary and domestication history 1 . Previous studies have rejected the idea of a single origin and instead support a model of mosaic genomic ancestry 2,3 . With increasingly comprehensive genome data, we now ask where the haplotypes — the building blocks of this mosaic — originate, and whether all domesticated barleys share the same wild progenitors or whether certain wild populations contribute more heavily to specific lineages. To address these questions, we apply a haplotype-based approach to investigate the genetic diversity and population structure of wild and domesticated barley. We analyse whole-genome sequences from 682 genebank accessions and 23 archaeological specimens, tracing the spatiotemporal origins of haplotypes and identifying wild contributors during domestication and later gene flow events. Ancient DNA supports our genome-wide findings from modern samples. Our results suggest that a founding domesticated population emerged in the Fertile Crescent during a prolonged period of pre-domestication cultivation. A key practical insight is that the high haplotype differentiation among barley populations — arising independently, or layered on top, of selection — poses challenges for mapping adaptive loci.